2022
DOI: 10.2967/jnumed.122.264112
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Whole-Body PET MRI Sequence Workflow in Pediatric Hodgkin Lymphoma Patients

Abstract: F-FDG PET/MRI might be the diagnostic method of choice for Hodgkin lymphoma patients, as it combines significant metabolic information from PET with excellent soft-tissue contrast from MRI and avoids radiation exposure from CT. However, a major issue is longer examination times than for PET/CT, especially for younger children needing anesthesia. Thus, a targeted selection of suitable whole-body MRI sequences is important to optimize the PET/MRI workflow. Methods: The initial PET/MRI scans of 84 EuroNet-PHL-C2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…In line with the current literature, both reading protocols had a high sensitivity, specificity, positive predictive value, negative predictive value, and accuracy above 89% concordant to previous publications [ 36 , 59 ]. Our results clearly support the increasing trend of MRI contrast agent–free [ 18 F]FDG PET/MR imaging in pediatric lymphoma patients [ 26 29 ]. This is from particular importance to skip the potential risk of gadolinium deposition to in the brain (dentate nucleus/paleostriatum) and bone due to repetitive application of linear, gadolinium-based contrast agents [ 23 , 24 , 60 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In line with the current literature, both reading protocols had a high sensitivity, specificity, positive predictive value, negative predictive value, and accuracy above 89% concordant to previous publications [ 36 , 59 ]. Our results clearly support the increasing trend of MRI contrast agent–free [ 18 F]FDG PET/MR imaging in pediatric lymphoma patients [ 26 29 ]. This is from particular importance to skip the potential risk of gadolinium deposition to in the brain (dentate nucleus/paleostriatum) and bone due to repetitive application of linear, gadolinium-based contrast agents [ 23 , 24 , 60 ].…”
Section: Discussionsupporting
confidence: 83%
“…The need for MRI contrast agent application in PET/MRI is clinically not debatable in individual tumor entities for further classification, such as liver or pelvic tumors [ 46 – 48 ]. Contrary, first publications have already shown that especially in pediatric lymphoma patients, a MRI contrast agent application might be waived for staging [ 13 , 29 ]. MRI contrast–free [ 18 F]FDG PET/MRI imaging protocols are able to outperform a radiation-saving [ 18 F]FDG PET/CT low-dose protocol with a more accurate soft tissue contrast and its well-known advantages when imaging parenchymal organs [ 13 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die Autoren kommen zu vergleichbaren Ergebnissen wie eine aktuelle Multicenterstu-die, die für pädiatrische Hodgkin-Lymphome publiziert wurde [5]. In beiden Studien konnte gezeigt werden, dass eine Kontrastmittelapplikation keine nennenswerten Vorteile beim Staging und bei der Response-Beurteilung bringt.…”
unclassified